(Mis)taking social responsibility? Implementing welfare state reform by private and non-profit organizations. Issue 12 (1st December 2020) - Gestel, Nicolette; Waldorff, Susanne Boch; Denis, Jean-Louis
ABSTRACT: This article relates institutional theory to the concept of organizational legitimacy with cognitive, moral, and pragmatic dimensions, to analyse how a Dutch national policy reform – aimed at expanding the social responsibility for sick leave and disability toward non-state organizations – is understood and enacted locally. Based on interviews in 52 organizations, the study highlights that implementing welfare state reform is predominantly based on pragmatic reasoning, and justified by specific moral and cognitive interpretations. The findings reveal that implementing reform is active institutional work by – paradoxically – restricted local agency, with disciplinary effects on a narrow range of actors.